2006
DOI: 10.1002/jcb.20883
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of anabolic signals and alteration of osteoblast nuclear morphology in microgravity

Abstract: Bone loss has been repeatedly documented in astronauts after flight, yet little is known about the mechanism of bone loss in space flight. Osteoblasts were activated during space flight in microgravity (microg) with and without a 1 gravity (1 g) field and 24 genes were analyzed for early induction. Induction of proliferating cell nuclear antigen (PCNA), transforming growth factor beta (TGFbeta), cyclo-oxygenase-2 (cox-2), cpla2, osteocalcin (OC), c-myc, fibroblast growth factor-2 (fgf-2), bcl2, bax, and fgf-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 42 publications
3
37
0
Order By: Relevance
“…DNA is also sensitive to weightlessness as the DNA spindle itself is a balanced structure. Changes in nuclear structure have been observed in previous weightlessness studies (Ingber, 1999;Hughes-Fulford et al, 2006). Such redistribu-…”
Section: A B Discussionsupporting
confidence: 60%
“…DNA is also sensitive to weightlessness as the DNA spindle itself is a balanced structure. Changes in nuclear structure have been observed in previous weightlessness studies (Ingber, 1999;Hughes-Fulford et al, 2006). Such redistribu-…”
Section: A B Discussionsupporting
confidence: 60%
“…Then, what will happen to bone cells after being submitted to mechanical unloading caused by weightlessness? In the past few years, people have paid more attention to the function of osteoblasts in responding to weightlessness (Hughes-Fulford et al 2006;Saxena et al 2007;Makihira et al 2008) Scientists have found that after space flight, some changes happen in cell morphology, cell proliferation, cell cycle, cellular cytoskeleton and gene expression in osteoblasts (Landis et al, 2000;Zerath et al 2000;Hughes-Fulford 2001;Doty 2004) Also many studies have investigated the effects of simulated weightlessness on osteoblasts under ground-based condition (Rucci et al 2007;Makihira et al 2008) In recent years, osteocytes have been thought to be as main coordinator responding to mechanical loading in bone tissue (Bonewald 2006(Bonewald , 2007. Osteocytes change their structure and functions after being submitted to mechanical stimulation (Zhang et al 2006;Skerry 2008;Tan et al 2008) Then, is it right that osteocytes also might play important role in responding to mechanical unloading such as weightlessness?…”
Section: Introductionmentioning
confidence: 99%
“…Bone-forming osteoblasts are vital factors in mechanosensing and mechanotransduction in vivo, and the biological responses of osteoblasts in altered gravity provide basic understanding of human bone loss in space. Osteoblasts in vivo and in vitro were found to be affected by low gravity [3][4][5][6]. The underlying mechanism of osteoblastic gravisensing and gravitransduction, however, remains poorly understood.…”
mentioning
confidence: 99%